ANALISIS YURIDIS PERLINDUNGAN KONSUMEN TERHADAP PENCANTUMAN LABEL DALAM BAHASA INDONESIA PADA KOSMETIK IMPOR UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Zaza Dwi Cahyono (Ensiklopedia of Journal, 2022)
This scientific work is entitled "Analysis of Juridical Labels In Indonesian Language On Imported Cosmetics To Realize Legal Certainty". The background of this paper is considering the large number of business actors who produce or trade imported cosmetic products in Indonesia without attaching labels in Indonesian to the imported cosmetic products, causing consumers to have difficulty understanding, using, and knowing the ingredients contained therein. . This study aims to provide an explanation regarding the legal regulation of labeling in Indonesian on imported cosmetics and to find out the implementation of obstacle factors and solutions for law enforcement of labeling in Indonesian on imported cosmetics by officers of the Sub-Directorate of Trade and Industry Ditreskrimsus Polda Riau Islands. This type of research is Field Study, and the approach used is Normative Empirical, data collection techniques through interviews with informants directly and looking for online data for secondary data, the results of which are directly analyzed through qualitative data. The results of this study indicate that BPOM's decision Number HK.00.05.4.1745 regarding cosmetics and the Regulation of the Food and Drug Supervisory Agency Number HK.03.1.23.12.10.12459 Year 2010 concerning Cosmetic Technical Requirements is the basis that requires imported cosmetic products circulating in Indonesia to contain the inclusion label in Indonesian on the imported cosmetic product. Second, the legal sanctions given can be in the form of administrative sanctions and criminal sanctions.Keywords: Inclusion, Indonesian Language, Import, Cosmetics